PENGARUH PENYULUHAN TERHADAP PENGETAHUAN TENTANG KANKER LEHER RAHIM PADA WANITA USIA SUBUR DI KELURAHAN BONGSARI SEMARANG BARAT TAHUN 2011 - Sri Wahyuni (Universitas Aisyiyah Yogyakarta, 2015)
The aim of research to determine the effect of education on knowledge of cervical cancer in women of childbearing age in the village of West Semarang Bongsari. A quasi-experimental research design with nonrandomized pre-post test control group. Sampling with purposive sampling. Data collection tool with a questionnaire. Data analysis used univariate analysis and multivariate analysis. The results of this research showed the proportion of education in both the treatment and control groups are equal. The pattern of such counseling is effective in increasing knowledge about cervical cancer, although only one extension. Intervention models give effect to increase knowledge about cervical cancer. In conclusion there was influence of education on knowledge of cervical cancer in women of childbearing age in the village of West Semarang Bongsari.Keywords: extension of cervical cancer, knowledge about cervical cancer, women of childbearing age